Dogs can detect the rust fungus Cronartium pini in the forest - Kaitera, Juha; Piri, Tuula; Männistö, Minna; Vinblad, Sanna; Väätäjä, Heli; Mäkitalo, Kari (Suomen metsätieteellinen seura, 2026)
Cronartium pini (Willd.) Jørst. is a major rust pathogen that kills especially Scots pine (Pinus sylvestris L.). Early diagnosis of the pathogen would reduce significant losses in managed forest productivity. Dogs (Canis lupus familiaris L.) with their accurate sense of smell have potential to detect forest pathogens at an early stage before they cause significant losses in forests. In this study, we tested in northern Finland whether trained volunteer dog-handler teams could identify infected wood, fruit bodies, spores or mycelia of C. pini in vitro and in vivo to facilitate early disease diagnosis. Volunteer dog-handler teams were able to indicate C. pini spores, fruit bodies and both fresh and old rust lesions on Scots pine including alive shoots, where the rust was present yet as latent. Five dogs out of five detected in vitro C. pini (both life-cycle forms), with 51% mean sensitivity and 58% mean precision. Four dogs out of four detected in vivo the autoecious life-cycle form of C. pini, with 95% mean sensitivity and 89% mean precision. In in vivo detection of the heteroecious life cycle form on pine, two dogs out of two performed with 78% mean sensitivity (100% precision). For identifying C. pini on alternate hosts in vivo, the mean sensitivity was 58% (precision 100%). Trained dog-handler pairs show promise as an aid in searching for C. pini especially in Scots pine stands at their early epidemical stage, but further testing is needed.
Keywords: pinus sylvestris; alternate hosts; resin-top disease; Scots pine blister rust; scent detection; canine